2016
DOI: 10.1128/aac.01471-16
|View full text |Cite
|
Sign up to set email alerts
|

Moxifloxacin Is a Potent In Vitro Inhibitor of OCT- and MATE-Mediated Transport of Metformin and Ethambutol

Abstract: c It is largely unknown if simultaneous administration of tuberculosis (TB) drugs and metformin leads to drug-drug interactions (DDIs). Disposition of metformin is determined by organic cation transporters (OCTs) and multidrug and toxin extrusion proteins (MATEsT uberculosis (TB) remains a leading cause of morbidity and mortality in developing countries, claiming over a million lives annually (1). Treatment of TB requires long and intensive combination drug therapy, which can be complicated by the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…2). The transport characteristics of ethambutol for OCT1 and OCT2 were consistent with a recent report, except for the multidrug and toxic compound extrusion (MATE) transporters (34). However, our study revealed that MATE transporters are unlikely to be involved with ethambutol transport and elimination from the kidney.…”
Section: Discussionsupporting
confidence: 91%
“…2). The transport characteristics of ethambutol for OCT1 and OCT2 were consistent with a recent report, except for the multidrug and toxic compound extrusion (MATE) transporters (34). However, our study revealed that MATE transporters are unlikely to be involved with ethambutol transport and elimination from the kidney.…”
Section: Discussionsupporting
confidence: 91%
“…Adjunctive therapy with host-modulating agents likely must strike a balance between an antimicrobial effect and excessive host inflammation, which may promote bacterial growth. Therefore, further preclinical pharmacokinetics studies of MetF coadministered with the first-line antitubercular regimen are urgently needed to guide the future study of this promising agent in clinical trials (19,20). In addition, detailed pharmacodynamics studies are required to relate plasma drug exposures in mice to AMPK activation and anti-TB activity in cell culture systems (6,21).…”
mentioning
confidence: 99%
“…Also, EMB absorption may be affected by uptake transporters, not simply passive diffusion, given EMB's low permeability into enterocytes (39). Recently, EMB has been reported to be a substrate of organic cation transporters (OCTs), multidrug and toxin extrusion proteins (MATEs), and P-gp (40,41). OCTs are known as uptake transporters expressed in various epithelial cells, such as intestine, liver, and lungs (30).…”
Section: Discussionmentioning
confidence: 99%